Cultural Hybridity and Identity Formation in Globalized Societies - Kipng'etich, Lewis (International Journal of Humanity and Social Sciences, 2024)
Purpose: The general purpose of the study was to explore cultural hybridity and identity formation in globalized societies. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to cultural hybridity and identity formation in globalized societies. Preliminary empirical review revealed that cultural hybridity was pervasive, with individuals blending diverse cultural influences to construct hybrid identities. Identity formation was dynamic and influenced by globalization, migration, and historical legacies. Power dynamics, including race and socio-economic status, intersected with cultural hybridity to shape experiences of identity and belonging. The study emphasized the importance of promoting inclusivity and dialogue to navigate the complexities of cultural hybridity and foster greater understanding across diverse cultural landscapes. Unique Contribution to Theory, Practice and Policy: The Post- Colonial theory, Intersectionality theory and Transnationalism theory may be used to anchor future studies on cultural hybridity and identity formation in globalized societies. The study provided valuable insights and recommendations that contributed to theory, practice, and policy. It enriched theoretical frameworks by adopting a multidimensional approach to understanding identity formation and underscored the importance of recognizing cultural diversity. Educators, community organizations, and policymakers utilized the study's findings to develop inclusive practices and policies that promoted intercultural understanding, social cohesion, and equitable access to resources. Additionally, media practitioners incorporated the study's insights to produce content that challenged stereotypes and fostered positive representations of cultural diversity. Overall, the study's recommendations have had a significant impact on efforts to promote inclusive development and intercultural dialogue in globalized societies.